Cover Picture: Synthesis and Thermal Responses of Polygonal Poly(ethylene glycol) Analogues (Chem. Asian J. 7/2016). Issue 7 (21st March 2016) - Kawasaki, Shunichi; Muraoka, Takahiro; Hamada, Tsutomu; Shigyou, Kazuki; Nagatsugi, Fumi; Kinbara, Kazushi
Abstract : A series of polygonal poly(ethylene glycol) (PEG) analogues with diagonal to hexagonal structures were synthesized. While pentagonal and hexagonal PEGs form aggregates in water at ambient temperature, trigonal and hexagonal PEGs show thermal responses to form or increase aggregates by temperature elevation. Relative hydrophobicity and molecular dynamics of these PEG analogues depend on the topology, likely resulting in their unique self‐assembling and thermal properties. More information can be found in the Full Paper by Takahiro Muraoka, Kazushi Kinbara et al. onpage 1028 in Issue 7, 2016 (DOI:10.1002/asia.201501381 ).